Fundamentals of Entrepreneurship (ENT300) : TD Fratello Printing Services / Afifah Athirah Saini ... [et al.] - Saini, Afifah Athirah; Clifton, Clarissa Eleanor; Bainon, Naidin Drew Ann; Salam, Nur Atikah; Basuini, Mohd Azizi (2019)
TD Fratello Printing Services have been established for 4 years up until know (since 20th July 2016). They are very famous for their fast customer service, in which customer are very satisfied for their art of work and quality in providing the best printing service. This company are focusing on providing trophies and medal service as their main product services. The reason is because, the high demand or highly requested in market. In addition, the company also provide printing clothes, banner, name tag, stamp and stickers alongside with stationary. The major problem they have face is lack of equipment or facilities in order to produce quality product and this led to affecting the productivity of their services